ANALYZING THE IMPACT OF WORK ENVIRONMENT AND ORGANIZATIONAL CULTURE ON EMPLOYEE JOB EFFECTIVENESS IN THE MAMUJU DISTRICT REGIONAL LIBRARY AND ARCHIVES OFFICE - Rosmawati S; Rohsita Amalyah Rasyid (SEAN Institute, 2023)
This research, conducted at the Office of the Regional Library and Archives Agency of Mamuju District, West Sulawesi, examines the factors influencing employee work effectiveness. Two primary independent variables, work environment and organizational culture, were investigated in relation to their impact on employee work effectiveness. The study found that both the work environment and organizational culture have a significant and positive influence on employee work effectiveness. Moreover, when considered simultaneously, these factors exert a substantial impact. The combined effect of the work environment and organizational culture accounts for 72.9% of the variation in employee work effectiveness. These findings emphasize the importance of addressing these factors to enhance employee performance and productivity. They provide valuable insights for organizations seeking to improve work effectiveness among their employees.